Meningkatkan Sikap Gotong Royong Melalui Metode PBL Dalam Pelajaran Pak Pada Siswa Fase B Kelas IV SD Negeri 01 Nanga Kantuk - Petronela Sarian; Andarweni Astuti (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2025)
This study is based on the experience that the attitude of mutual cooperation of students in learning Catholic Religious Education in sikap gotong royongade IV students of SD Negeri 01 Nanga Kantuk is still low. This is reflected in the discussion activities carried out by students. Most students have not been able to show an attitude of cooperation, care, and sharing in completing a learning topic. Therefore, this study aims to apply the Problem Based Learning (PBL) model in improving students' mutual cooperation attitudes in learning. This research is a classroom action research (PTK) which is carried out in two cycles. Each cycle consists of the planning, implementation, observation, and reflection stages. Data were collected through observation, questionnaire sheets, and documentation. The subjects of the study were sikap gotong royongade IV students with a total of 15 students. The results of the study showed that the application of the PBL model can significantly improve students' mutual cooperation attitudes in learning. In cycle I, students' mutual cooperation attitudes in learning were still quite good with an average of 52%. After the strategy was improved in the second cycle, students' mutual cooperation attitudes increased to 75%. This means that there was an increase of 23%. This shows that the application of the PBL model in learning can improve students' mutual cooperation attitudes.